Cold spray coating: review of material systems and future perspectives - Moridi, A.; Hassani-Gangaraj, S. M.; Guagliano, M.; Dao, M. (Surface engineering, 2014)
Cold gas dynamic spray or simply cold spray (CS) is a process in which solid powders are accelerated in a de Laval nozzle toward a substrate. If the impact velocity exceeds a threshold value, particles endure plastic deformation and adhere to the surface. Different materials such as metals, ceramics, composites and polymers can be deposited using CS, creating a wealth of interesting opportunities towards harvesting particular properties. CS is a novel and promising technology to obtain surface coating, offering several technological advantages over thermal spray since it utilizes kinetic rather than thermal energy for deposition. As a result, tensile residual stresses, oxidation and undesired chemical reactions can be avoided. Development of new material systems with enhanced properties covering a wide range of required functionalities of surfaces and interfaces, from internal combustion engines to biotechnology, brought forth new opportunities to the cold spraying with a rich variety of material combinations. As applications multiply, the total number of studies on this subject is expanding rapidly and it is worth summarizing the current state of knowledge. This review covers different material systems that have been studied up to now with an emphasis on potential innovative applications. This includes metallic, ceramic and metal matrix composite (MMC) coatings and their applications. Polymer (both as substrate and coating) and metal embedment in the polymer are also covered. CS has emerged as a promising process to deposit nanostructured materials without significantly altering their microstructure whereas many traditional consolidation processes do. Relevant material systems containing nanostructured powders are also considered. A critical discussion on the future of this technology is provided at the final part of the paper focusing on the microstructural bonding mechanisms for those relatively less explored material systems. These include MMCs involving more than one constituent, ceramics, polymers and nanostructured powders. Future investigations are suggested especially to quantitatively link the process parameters and the behaviour of the material systems of interest during impact.